Labour as a utility measure reconsidered - Michael Ahlheim; Oliver Frör; Nguyen Minh Duc; Antonia Rehl; Ute Siepmann; Pham Van Dinh (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
In Stated Preference studies for the appraisal of environmental projects in poor countries or regions it often turns out that the stated willingness to pay of people for environmental improvements, which is used as measure of individual welfare changes, is very low. This is often interpreted as the result of extremely tight budget constraints, which make it impossible that people express their true appreciation of an environmental project in terms of their willingness to pay for it. Therefore, it is sometimes suggested to use labour contributions instead of money as a numeraire to measure utility in such studies. In this paper we show theoretically and empirically that this suggestion is not compatible with the principles of welfare theory because of several inconsistencies. We also illustrate the validity of our arguments empirically based on the results of a Contingent Valuation study conducted in a rural area in northern Vietnam.
urn:nbn:de:bsz:100-opus-13329
Keywords: D61; H43; Q51; 330; Contingent Valuation; Cost-benefit Analysis; Developing Countries; Public Expenditures; Vietnam; Willingness to work